The Effect of Audit Findings and Audit Opinions on the Level of Corruption of the Regional Government of Lampung Province - Safitri, Yuyun; Barusman, Andala Rama Putra (LPPPIPublishing, 2025)
This study aims to examine the effect of Audit Findings and Audit Opinions on the Corruption Level of the Regional Government of Lampung Province. The population of this study is the Regional Government of Lampung Province. The variables analyzed include Audit Findings which serve as an important tool to identify and reduce corrupt practices and Audit Opinions which highlight the important role of audit opinions. The multiple regression analysis method was used to see the influence of the two variables on the Corruption Level. The results showed that partially Audit Findings have a significant effect on the Corruption Rate, while Audit Opinions do not have a significant effect on the Corruption Rate. In addition, it simultaneously shows that both variables have a significant effect on the Corruption Rate. These findings indicate that audit findings have a greater effect on increasing the amount of corruption than Audit Opinions. Therefore, researchers suggest that the government needs to improve follow-up on audit findings that reveal irregularities in the management of government budgets or activities, implementing an effective system for following up on audit results will strengthen supervision and minimize opportunities for corruption.